Pomegranate Seed Oil and Bitter Melon Extract Affect Fatty Acids Composition and Metabolism in Hepatic Tissue in Rats - Agnieszka Stawarska; Tomasz Lepionka; Agnieszka Białek; Martyna Gawryjołek; Barbara Bobrowska-Korczak (Molecules, 2020)
Pomegranate seed oil (PSO) and bitter melon dried fruits (BME) are used as natural remedies in folk medicine and as dietary supplements. However, the exact mechanism of their beneficial action is not known. The aim of study was to assess how the diet supplementation with PSO and/or with an aqueous solution of Momordica charantia affects the metabolism of fatty acids, fatty acids composition and the level of prostaglandin E2 (PGE2) in rat liver. Animals (Sprague-Dawley female rats, n = 48) were divide into four equinumerous groups and fed as a control diet or experimental diets supplemented with PSO, BME or both PSO and BME for 21 weeks. Fatty acids were determined using gas chromatography with flame ionization detection. PSO added to the diet increased the rumenic acid content (p < 0.0001) and increased accumulation of n-6 fatty acids (p = 0.0001) in hepatic tissue. Enrichment of the diet either with PSO or with BME reduced the activity of Δ6-desaturase (D6D) (p = 0.0019), whereas the combination of those dietary factors only slightly increased the effect. Applied dietary supplements significantly reduced the PGE2 level (p = 0.0021). No significant intensification of the influence on the investigated parameters resulted from combined application of PSO and BME. PSO and BME have potential health-promoting properties because they influence fatty acids composition and exhibit an inhibiting effect on the activity of desaturases and thus they contribute to the reduction in the metabolites of arachidonic acid (especially PGE2).